Secondary osteoporosis in patients with chronic obstructive lung disease - N. L. Shaporova; V. I. Trofimov (Медицинский совет, 2013)
Osteoporosis (OP) is a progressive multifactorial systemic skeletal disease resulting from a loss of bone mass and damage of bone structure (microarchitectonics). Chronic obstructive pulmonary disease (COPD) and bronchial asthma (BA) are major contributors to the development of osteoporosis.